Faktor yang Memengaruhi Status Gizi pada Balita di Wilayah Kerja Puskesmas Perawatan Pining Kecamatan Pining Kabupaten Gayo Lues Kota Aceh - Nona Juli Piarni; Nur Aini; Ramadhani Syafitri Nasution (Universitas Muhammadiyah Manado, 2025)
Nutrition status is a condition of the body as a result of food consumption and the use of nutrients that are very much needed by the body as a source of energi, grouth and maintenance of body tissues, and regulators of body processes. The purpose of this study was to determine the factors that influence malnutrition in toddlers in the Pining Health Center Work Area, Pining District, Gayo Lues Regency, Aceh City. The type of research is quantitative with a cross-sectional design. The population in this study was 234 respondents with the sample being the purposive sampling. Data analysis used univariate, biavariate analysis using chi-square and multivariate test statistik with logistic regression test statistics at a confidence level of 95% (α=0.05). Based on the research results, it shows that there is an infuluence of feeding practices (p=0.002), parenting practices (p=0.002), hygiene practices (p=0.001), and health care practices (p=0.008) on malnutrition in toddlers in the Pining Health Center Work Area, Pining District, Gayo Lues Regency, Aceh City. The conclusion of this study is that health care practices are the most influence with malnutrition. It is recommended to increase community empowerment in each village in malnutrition to improve nutrition and improve the health of the community, especially toddlers who are malnourished.